2004
DOI: 10.1016/j.apm.2004.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of mould wall roughness on the melt flow simulation in casting process

Abstract: In this investigation a computational model has been developed which includes heat and mass transfer as well as effects of backpressure, and mould wall friction for the simulation of incompressible flow with free surfaces in mould cavity filling. The simulation of flow with free surfaces is based on the SOLA-VOF numerical algorithm, utilizing the finite difference method. The solid and free boundary conditions have been modified and a new algorithm has been developed to calculate the effect of cavity pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 9 publications
0
20
0
1
Order By: Relevance
“…Pequet et al [6] studied the defects formation during solidification of Al alloy using ABAQUS and showed that most of the defects formed where the metal solidified last. Mirbagheri et al [7] has studied the melt flow and effect of mould roughness of sand mould. Computational results were verified by casting of an aluminum alloy within a transparent mould and the mould erosion at different times has been recorded.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pequet et al [6] studied the defects formation during solidification of Al alloy using ABAQUS and showed that most of the defects formed where the metal solidified last. Mirbagheri et al [7] has studied the melt flow and effect of mould roughness of sand mould. Computational results were verified by casting of an aluminum alloy within a transparent mould and the mould erosion at different times has been recorded.…”
Section: Literature Reviewmentioning
confidence: 99%
“…В ра-ботах [3,4] проведено исследование процесса заполнения вязкопластичной средой осесим-метричных объемов методом литья под давлением. Задача о заполнении прямоугольных каналов ньютоновской жидкостью в случае, когда направления движения и силы тяжести совпадают, рассматривалась в [5][6][7], а в случае, когда они противоположны, -в [8][9][10][11].…”
unclassified
“…CFD has been extensively used in metal casting and simulating the flow of molten metals in moulds. [3][4][5][6] Reilly et al 7,8 have critically reviewed the role of CFD in defect entrainment in the shape casting process and summarized different numerical approaches used in different commercial packages, that is, MAGMASOFT 9 and FLOW-3D. 10 Another example of fluid flow analysis in modelling of manufacturing processes has been given by Zhang and Wu, 11 in which they investigated the effect of fluid flow in the weld pool on the numerical simulation accuracy of the thermal field in hybrid welding.…”
Section: Introductionmentioning
confidence: 99%